Application Of Data Mining On Sidoarjo Leather Crafts Sales With Apriori Algorithm To Assist Marketing Strategies: Penerapan Data Mining Pada Penjualan Kerajinan Kulit Sidoarjo Dengan Algoritma Apriori Untuk Membantu Strategi Pemasaran - Muhamad Alfin Firdiansyah; Yulian Findawati (Academia Open, 2021)
Sidoarjo is one of the regencies that is developing in a forward direction. This is known by the increase in the tourism sector and Small and Medium Enterprises. One of them is Sidoarjo leather handicraft. UD Qory Jaya is a business actor in the leather retail industry. Orders that continue to increase make the turnover of goods uneven resulting in a buildup of stock in stores. Due to these problems the compilers took the initiative to deliver messages by carrying out a method of processing data using the Apriori algorithm. This method is used to maximize the sales potential of a combination system of goods so that the target item for sale is appropriate. From the results of research conducted by testing a minimum support of 15% and a minimum of 20% confidence, the association rules are produced if you buy a slingbag then buy men's leather shoes and vice versa. And from the test results with a minimum support of 70% and a minimum confidence of 70% an association rule is not generated because the existing data does not exceed the minimum value of support and minimum confidence. With the implementation of this method, researchers hope to have a better impact for developing future marketing strategies based on previously researched data.